A Study to Elicit Behavioral Health Patients' and Providers' Opinions on Health Records Consent. Issue 2 (2017) - Grando, Maria Adela; Murcko, Anita; Mahankali, Srividya; Saks, Michael; Zent, Michael; Chern, Darwyn; Dye, Christy; Sharp, Richard; Young, Laura; Davis, Patricia; Hiestand, Megan; Hassanzadeh, Neda
Abstract : A main objective of this study is to assess the opinions of 50 behavioral health patients on selective control over their behavioral and physical health information. We explored patients' preferences regarding current consent models, what health information should be shared for care and research and whether these preferences vary based on the sensitivity of health information and/or the type of provider involved. The other objective of this study was to solicit opinions of 8 behavioral health providers on patient-driven granular control of health information and potential impact on care. Electronic surveys were implemented at an outpatient Behavioral Health facility that provides care for behavioral health patients with non-serious mental illnesses. The Patient Survey included questions regarding patients' demographics and about their concerns and preferences for data sharing for care and research. The Provider Survey included questions about their view on the current consent process and perceptions on barriers and facilitators to implement patient-controlled granular consent models. This novel study provides valuable preliminary data that can help guide future studies to better understand privacy choices of this underrepresented patient group.